The Role of Villlage Government and Benefits (MTQ) Musabaqah Tilawatil Qur’an Towards Change Management Balinggi District Parigi Moutung Regency - Awaluddin; Mutmainnah (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
Balinggi District achieved a brilliant accomplishment by winning the Overall Champion title at the 18th Musabaqah Tilawatil Qur'an (MTQ) at the Regency Level of Parigi Moutong (Parimo) in 2024, held from December 16 to 21, 2024. This study aims to: (1) examine the role of MTQ as a means of implementing and understanding the Qur’an in daily life, (2) describe community participation in preserving the Qur’an as a life guide, and (3) analyze the government’s role in enhancing interfaith harmony. The research uses a qualitative-quantitative descriptive method without hypotheses (Andra Tersiana, 2023), with data collected through surveys and interview questionnaires involving 50 respondents. The findings reveal: (A) Respondent demographics were predominantly male (64%), aged 41–50, with high school/bachelor’s education, working as civil servants/non-civil servants (62%), and earning middle-income (72%). (B) The village government’s role in preparing venues and supporting MTQ performance was highly rated, with 74% of respondents strongly agreeing. (C) The district government’s efforts in improving collaboration and service quality for MTQ received positive feedback, with 68% strongly agreeing. (D) The Religious Affairs Office’s (Kemenag) provision of MTQ facilities was deemed satisfactory, with 76% strongly agreeing. The study concludes that MTQ serves not only as a competition but also as a platform for religious reinforcement, community engagement, and government synergy in fostering social harmony.